Estimation of ecosystem biodiversity using geographic information technologies - Omelych, I.Y.; Neposhyvailenko, N.O. (Problems of Environmental Biotechnology, 2023)
This study focuses on the analysis of the ecosystem of the Oril river catchment area within the Dnipro region, where biodiversity is a critical issue and natural resource conservation is of particular relevance.